Callus Induction and Plant Regeneration in Rauvolfia Serpentina (L.) Benth Ex. Kurz. - Aryal, Saraswoti; Joshi, Sanu Devi (Journal of Natural History Museum, 2009)
Rauvolfia serpentina (L.) ex. Kurz is an important medicinal plant. Callus induction and regeneration was studied from stem explant of in-vitro grown plant of Rauvolfia serpentina(L.) Benth. ex Kurz (Apocynaceae) on Murashige Skoog (1962) medium supplemented with 1mg/l 2,4-Dichlorophenocy acetic acid (2,4-D) and 1mg/l Kinetin (Kn). Vigorous growth of callus occurs after 4 weeks of culture. Callus was sub-cultured on Murashige and Skoog (MS) medium supplemented with different concentration of 2, 4-D (0.5-3.0 mg/l) and 10% coconut milk. Regeneration of plantlets occurred on MS medium containing 3 mg/1 of 2, 4-D and 10% coconut milk. These plantlets were rooted on MS medium supplemented with 1 mg/l IAA .The regenerated plantlets were able to grow on soil after short period of acclimatization. Key words: Explant; In-vitro culture; MS medium; 2, 4 Dichlorophenoxy acetic acid; Kinetin; Callus; Tissue culture; Coconut milk. <!--[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Journal of Natural History Museum Vol. 24, 2009 Page: 82-88